PENGARUH PERILAKU ALTRUISME DAN DUKUNGAN SOSIAL ORANG TUA TERHADAP PSYCHOLOGICAL WELL BEING MELALUI INTERNALISASI NILAI PENDIDIKAN AGAMA ISLAM PADA SISWA SMP NEGERI 2 KECAMATAN LUAK - Dessy Maulana; Afrinaldi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of parental altruism and social support on the psychological well-being of students at SMP Negeri 2 in Luak Subdistrict. This study employs a quantitative approach with a correlational design. The population of this study consists of all 111 students at SMP Negeri 2 in Luak Subdistrict, with a sample size of 87 students. The research instrument consists of a questionnaire based on a Likert scale. Data analysis methods included multiple linear regression and partial regression tests to determine the effects of the independent variables on the dependent variable, as well as a simultaneous regression test to determine the combined effect of both independent variables on the dependent variable. Additionally, the researcher conducted a coefficient of determination test to indicate the percentage of the dependent variable that can be explained by the independent variables. The results of the study indicate that altruistic behavior has a positive and significant effect on psychological well-being. Parental social support also has a positive and significant effect on students’ psychological well-being. Simultaneously, altruistic behavior and parental social support have a positive and significant effect on students’ psychological well-being.